[Afisz. Incipit] Mecz Bokserski M.K.S. Gdynia - K.K.S. Unia Tczew ... (Tczew : [wydawca nieznany], 1947)
Afisz informujący o meczu, który odbył się 19.04.1947 r. w sali św. Józefa (Nowemiasto).
Keywords: Boks -- Polska -- 1945-1990 -- druki ulotne; Tczew (Polska) -- 1945-1970 -- druki ulotne; Afisze -- 1945-1990.